A Review of Bat Fleas (Siphonaptera: Ischnopsyllidae) from Russia - Maria V. Orlova; Alex L. Viskontene; Vyacheslav A. Korzikov; Marina V. Zabashta; Alexey V. Zabashta; Sergei V. Kruskop; Dmitriy G. Smirnov; Maria S. Malyavina; Alexandr V. Pavlov; Oleg L. Orlov; Vladimir A. Mishchenko; Ivan V. Vyalykh; et al. (Diversity)
Eighteen flea species of four genera associated with bats (Chiroptera: Vespertilionidae, Rhinolophidae, Miniopteridae, Molossidae) are registered in Russia, based on a literature review as well as our own data. They are as follows: Myodopsylla trisellis, Ischnopsyllus (Ischnopsyllus) dolosus, Ischnopsyllus (I.) elongatus, Ischnopsyllus (I.) intermedius, Ischnopsyllus (I.) plumatus, Ischnopsyllus (I.) needhami, Ischnopsyllus (I.) obscurus, Ischnopsyllus (I.) octactenus, Ischnopsyllus (I.) simplex, Ischnopsyllus (I.) variabilis, Ischnopsyllus (Hexactenopsylla) hexactenus, Ischnopsyllus (H.) petropolitanus, Ischnopsyllus (H.) ussuriensis, Ischnopsyllus (H.) comans, Nycteridopsylla pentactena, Nycteridopsylla longiceps, Nycteridopsylla eusarca, Rhinolophopsylla unipectinata unipectinata. Ischnopsyllus (I.) elongatus and Ischnopsyllus (I.) octactenus were recorded in Kaluga Region and Vladimir Region for the first time. Ischnopsyllus (I.) variabilis in Kaluga Region is a newly documented find. Studied bat flea fauna exhibits a distinctly Western Palearctic appearance.